Nested Socio-Ecological Maps as a Spatial Planning Instrument for Estuary Conservation and Ecosystem-Based Management - Galván, Cristina; Puente, Araceli; Juanes, José A. (Frontiers in Marine Science, 2021)
Estuaries are socio-ecological systems that can be represented as a holistic combination of biotic and abiotic conditions in spatially explicit units defined by: (i) the ecotope, as the integration of the physiotope (abiotic-homogeneous units) and the biotope (biotic-homogeneous units), and (ii) the anthrotope, synthesizing data on human drivers of ecological change. Nested physiotopes were identified in an estuary using a hierarchical approach that integrates information about eight abiotic, and biologically meaningful, variables. The biotope of Zostera noltei was delimited using a potential distribution model of species and overlapped with the physiotope map to characterize the ecotopes. The anthrotope was estimated as the cumulative impacts of anthropic activities over the ecotopes. The diversity of Z. noltei ecotopes was compared with the anthrotope map to estimate the potential impacts of human pressures on this species. The hierarchical methodology and resulting maps provide flexible and interdisciplinary tools for conservation, management, education and research.